2000
DOI: 10.2337/diabetes.49.3.424
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of INS-1-derived cell lines with robust ATP-sensitive K+ channel-dependent and -independent glucose-stimulated insulin secretion.

Abstract: The biochemical mechanisms involved in regulation of insulin secretion are not completely understood. The rat INS-1 cell line has been used to gain insight in this area because it secretes insulin in response to glucose concentrations in the physiological range. However, the magnitude of the response is far less than that seen in freshly isolated rat islets. In the current study, we have stably transfected INS-1 cells with a plasmid containing the human proinsulin gene. After antibiotic selection and clonal ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
801
1
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 832 publications
(820 citation statements)
references
References 27 publications
16
801
1
2
Order By: Relevance
“…INS832/13 cells [42] (passages were grown in monolayer cultures as described previously [43]. This was done in a humidified (5% CO 2 , 95% air) atmosphere at 37°C in regular RPMI 1640 medium supplemented with 10 mmol/l HEPES, 10% FCS, 2 mmol/l L-glutamine, 1 mmol/l sodium pyruvate, 50 µmol/l β-mercaptoethanol (referred to below as complete medium).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…INS832/13 cells [42] (passages were grown in monolayer cultures as described previously [43]. This was done in a humidified (5% CO 2 , 95% air) atmosphere at 37°C in regular RPMI 1640 medium supplemented with 10 mmol/l HEPES, 10% FCS, 2 mmol/l L-glutamine, 1 mmol/l sodium pyruvate, 50 µmol/l β-mercaptoethanol (referred to below as complete medium).…”
Section: Methodsmentioning
confidence: 99%
“…This was done in a humidified (5% CO 2 , 95% air) atmosphere at 37°C in regular RPMI 1640 medium supplemented with 10 mmol/l HEPES, 10% FCS, 2 mmol/l L-glutamine, 1 mmol/l sodium pyruvate, 50 µmol/l β-mercaptoethanol (referred to below as complete medium). This clone (832/13) of the INS-1 cell was used because it shows better differentiation characteristics in terms of glucose-stimulated insulin secretion than the original INS-1 cell line [42].…”
Section: Methodsmentioning
confidence: 99%
“…Clonal INS-1 832/13 cells expressing the human insulin gene (a gift from Dr Christopher Newgard, Duke University), 14 were grown in culture at 37°C, 5% CO 2 in 75 cm 2 cell culture T-flasks (Corning Inc., Corning, NY). Standard RPMI-1640 culture medium (Sigma-Aldrich, St. Louis, Mo) was supplemented with 10% fetal calf serum (Mediatech, Herndon, Va), 10 mmol/L HEPES (Media-tech), 2 mmol/L L-glutamine (Sigma-Aldrich), 1 mmol/L sodium pyruvate (Sigma-Aldrich), and 50 μmol/L 2-mercaptoethanol (Sigma-Aldrich).…”
Section: Ins-1 Cell Culture and Human Islet Isolation And Culturementioning
confidence: 99%
“…After 2 minutes of incubation, trypsin was neutralized with 6 mL of standard serum-supplemented culture media. 14 The cell suspension was then transferred to a 15-mL conical tube and placed into a 60 °C water bath for 60 minutes. For time course experiments, aliquots of INS-1 cells were removed from the 15-mL conical tube at specified timepoints (1,3,5,25, and 47 hours).…”
Section: Heat Treatment Of Ins-1 Cells and Human Isletsmentioning
confidence: 99%
“…Interestingly, in a recent study Neve et al [10] reported a high glucoseinduced stimulation of KLF11 mRNA expression in INS832/13 beta cells. This opposing observation may be explainable by possible differences between native INS-1E beta cells used in our study and the INS832/13 beta cell line, which is derived from a highly selected INS-1 subclone stably transfected with a plasmid containing the human proinsulin gene [16]. More importantly, Neve et al [10] demonstrated activation of hInsP by cotransfected FLAG-tagged KLF11 in beta-TC3 beta cells.…”
Section: Discussionmentioning
confidence: 67%